Pharmacokinetics and Main Metabolites of Anwulignan in Mice - Chen, Cong; Feng, Yanbo; Li, Han; Lin, Hao; Jing, Shu; Li, He; Wang, Chunmei; Chen, Jianguang; Sun, Jinghui (Frontiers in Pharmacology, 2022)
Anwulignan is a representative component of Chinese traditional medicine Schisandra sphenanthera, with strong pharmacological activities. However, there are few reports on its pharmacokinetics and metabolites in the body. In this study, a metabolomic method based on UHPLC-Q-Orbitrap-MS was used to study the pharmacokinetics of anwulignan in the blood, organs, urine and feces samples of mice after the intragastric administration of anwulignan (10 mg/kg). The pharmacokinetic parameters were calculated, and the distribution characteristics and main metabolites of anwulignan in the body of mice were analyzed. The results showed that the retention time of anwulignan in the body of mice was longer (t1/2 = 7.1 h), and anwulignan was widely distributed in the body (Vz/F = 32.81 L/kg), especially in the liver. The order of anwulignan concentration in the tissues of mice from high to low was the liver > heart > brain > kidney > lung > spleen. Anwulignan was mainly excreted through the digestive tract in the form of its prototype and metabolites, indicating that it might experience an enterohepatic circulation. A total of 7 metabolites were identified, and the demethylation, hydroxylation, dehydroxylation and demethoxylation were considered to be the main metabolic ways of anwulignan in the body of mice.